Effect of promotion factors toward the level of customer awareness of REMIX magazine published by Utusan Melayu (Malaysia) Berhad at Bandar Baru Bangi in year 2008 / Nur Farhana Omar - Omar, Nur Farhana (Faculty of Business and Management, 2018)
This research conducted focusing on the "The Effect of Promotion Factors toward Level of Customer Awareness of REMIX Magazine". As a new magazine in the industry, Utusan Melayu realizes that customer awareness is very important to ensure the successful of REMIX magazine performances in term on sales. The main objective of this study are (1) to identify the level of customer awareness toward REMIX magazine, (2) to determine which promotion factors such as choice of promotion tools, frequency of promotion activities and creativity of promotion activities that influence customer awareness, (3) to identify which promotion's factor the most influence customer awareness and (4) to suggest an improvement of promotion factors provided by Utusan Melayu (Malaysia) to increase level of customer awareness.